Enhancement of magnetic properties in hard/soft CoFe2O4/Fe3O4 nanocomposites. Issue 52 (10th May 2016) - Zeng, Qingzi; Jiang, Dongmei; Yang, Shengbin
Abstract : Significant enhancements of M r / M s ratio, H c and (BH)max have been achieved in the CoFe2 O4 /Fe3 O4 nanocomposites compared with the pure CoFe2 O4 . Abstract : CoFe2 O4 /Fe3 O4 nanocomposites with different concentrations of soft ferrite (Fe3 O4 ) were fabricated using a co-precipitation method. Crystal structure, phase composition, morphology and magnetic properties of as-synthesized nanocomposites were characterized by X-ray diffraction (XRD), inductively coupled plasma (ICP), Mössbauer spectroscopy (MS), scanning electron microscopy (SEM), transmission electron microscopy (TEM) and vibrating sample magnetometer (VSM). Results from XRD and MS reveal that the nanocomposites are composed of two phases (CoFe2 O4 and Fe3 O4 ), both of which have a spinel structure. SEM and TEM show that the average particle size of the nanocomposites is about 20 nm. VSM indicates that all hysteresis loops exhibit a single-phase-like behaviour. The remanence ratio ( M r / M s ), coercivity ( H c ) and maximum magnetic energy product (BH)max are significantly enhanced in all the nanocomposites compared with pure hard ferrite (CoFe2 O4 ). The enhancement of the magnetic properties may be attributed to the exchange coupling interaction in the system.